Penerapan Metode Belanja Barang dan Jasa Pemerintah Melalui Sistem E-Purchasing (E-katalog) di RSUD Dr. Soetomo - Paryono; Zaman, Komarun; Megasari, Aisyah Darti (Jurnal Pengadaan Barang dan Jasa, 2025)
This study aims to describe the implementation of the government procurement method for goods and services through the e-purchasing system (e-catalog) at Dr. Soetomo Regional General Hospital. The data reviewed are a summary of procurement methods and types. Data collection techniques used include interviews, observation, and documentation. Qualitative data analysis was used. The results of this study indicate that the e-catalog system is simple, effective, efficient, and on-target. The e-catalog has problems such as frequent application errors, unmet product needs, and the inability to provide services within the specified timeframe without a contract. Criteria for selecting goods and services providers include licensing, good reviews, and product prices that meet requirements. Late delivery or exceeding the deadline is subject to sanctions. The benefits of the e-catalog simplify the monitoring and maintenance process, as it facilitates communication between all parties involved. Its advantages include ensuring the certainty of the technical specifications of the goods or services ordered and ensuring appropriate prices.